1998
DOI: 10.1267/ahc.31.401
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Biological Aggressiveness of Bone Giant Cell Tumor by the Comparative Study of Immunohistochemical Detection of DNA-instability and Cortical Bone Destruction by CT.

Abstract: The degree of DNA-instability as revealed by the immunohistochemical staining with anti-single-stranded DNA antibody after acid hydrolysis (DNA-instability test) was used as a marker of malignancy. This was applied to benign (4 osteochondroma and 4 enchondroma cases), border-line (23 bone giant cell tumor, BGCT cases), and malignant (6 chondrosarcoma and 6 osteosarcoma cases) neoplastic lesions. The expression of tumor oncogene, c-myc was detected immunohistochemically.Proliferative activity was evaluated by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In these studies, and also in the present study, the DNA-instability-positive lesions showed significantly higher values of positivity of other biomarkers. Furthermore, many abnormal mitoses were found predominantly in the DNA-instability test-positive lesions as shown in the present study (Figure 2) and other reports (Tsuzuki et al, 1994;Azuchi et al, 1998); and the frequency of chromosome 17 polysomies and the percentage of hyperdiploid cells measured by means of the chromosome index using interphase cytogenetics increased significantly and exclusively in the DNA-instability test-positive lesions (Khaled et al, 2000;Ishida et al, 2001). This is also supported by the report that numerical chromosomal aberration is associated with cancer progression (Bulten et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In these studies, and also in the present study, the DNA-instability-positive lesions showed significantly higher values of positivity of other biomarkers. Furthermore, many abnormal mitoses were found predominantly in the DNA-instability test-positive lesions as shown in the present study (Figure 2) and other reports (Tsuzuki et al, 1994;Azuchi et al, 1998); and the frequency of chromosome 17 polysomies and the percentage of hyperdiploid cells measured by means of the chromosome index using interphase cytogenetics increased significantly and exclusively in the DNA-instability test-positive lesions (Khaled et al, 2000;Ishida et al, 2001). This is also supported by the report that numerical chromosomal aberration is associated with cancer progression (Bulten et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Based on the finding that all cancerous cells produce much more single-stranded DNA than normal cells after acid hydrolysis, Fukuda et al (1986Fukuda et al ( , 1993 developed the method of staining cancerous cells specifically with acridine orange or anti-cytidine antibody after acid hydrolysis and called it as the DNA-instability test as a specific marker for malignancy irrespective of epithelial or mesenchymal origin. Since the first report (Fukuda et al, 1986), more than 20,000 malignancy cases and socalled borderline malignancy cases were tested by this method (Nitta et al, 1993;Otaki et al, 1994;Tsuzuki et al, 1994;Azuchi et al, 1998;Khaled et al, 2000;Hirai et al, 2001;Ishida et al, 2001;Iwasa et al, 2001), and all cancerous cells were found to be positively stained in the DNA-instability test, while comparable normal cells, vascular endothelial cells, fibroblasts and inflammatory cells present in the same slides were completely negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA-instability-test has been proposed by us as a specific marker of malignancy, irrespective of the epithelial or mesenchymal origin of tumors (Fukuda et al, 1986(Fukuda et al, , 1993Nitta et al, 1993;Otaki et al, 1994;Tsuzuki et al, 1994;Azuchi et al, 1998;Khaled et al, 2000). The method of differentially staining malignant cells either with acridine orange or anti-single-stranded DNA is based on the abundant production of denatured singlestanded DNA in cancerous cells after acid hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…They also developed the method of differential fluorescent or immunohistochemical staining of cancerous cells after denaturation of nuclear DNA by acid hydrolysis. By using this method (the DNA instability test), cancerous clones could be identified during early stages of carcinogenesis in so-called borderline or precancerous lesions such as colorectal adenoma (Nitta et al, 1993), gastric adenoma (Otaki et al, 1994), otorhinolaryngeal borderline lesions (Tsuzuki et al, 1994), bone giant cell tumours (Azuchi et al, 1998), and uterine cervical dysplasia (Khaled et al, 2000).…”
Section: Introductionmentioning
confidence: 99%